Sulfide solid electrolyte and preparation method and application thereof

By introducing M metal elements into the sulfide solid electrolyte and controlling its lattice structure, the problem of low ion conductivity of the existing sulfide solid electrolyte is solved, and higher lithium ion conductivity and battery performance are achieved.

CN119542516APending Publication Date: 2025-02-28HONG KONG QUANTUM AI LAB LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411862610.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing sulfide solid electrolyte has low ionic conductivity, which limits its application in actual batteries.

Method used

By introducing M metal elements, the lattice structure of the sulfide solid electrolyte is regulated, thereby improving the lithium ion conductivity. The specific method includes mixing lithium source, phosphorus source, M source, sulfur source and X source for ball milling and vacuum calcining to form a sulfide solid electrolyte with a Li5+(5-b)aP1-aMaS4X2 structure.

Benefits of technology

The ionic conductivity of the sulfide solid electrolyte is improved, and the charging and discharging rate, power density and overall performance of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542516A_ABST
    Figure CN119542516A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfide solid electrolyte as well as a preparation method and application thereof, and relates to the technical field of lithium ion batteries, the composition of the sulfide solid electrolyte is Li < 5 + (5-b) P < 1-a > MaS < 4 > X < 2 >, wherein M comprises at least one of alkali metal, alkaline earth metal and transition metal; x is one or more of F, Cl and Br; the value range of a is 0 lt; a < lt >; the value range of 1 and b is 0 lt; blt; 5. Wherein M metal element doping can improve the stability of the sulfide solid electrolyte on one hand; on the other hand, the movement modes of other elements in crystal lattices can be regulated and controlled, so that the lithium ion conductivity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly to a sulfide solid electrolyte, a preparation method thereof, and an application thereof. Background Art

[0002] A solid-state electrolyte (SSE) refers to a solid material used as an ion conductor in an electrochemical device. Compared with traditional liquid electrolytes, it has higher safety, a wider operating temperature range, and better mechanical stability.

[0003] Solid-state electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and polymer-based solid electrolytes. Among them, sulfide-based solid electrolytes such as LPS (Li2S-P2S5) have good flexibility and are easy to be processed into thin films.

[0004] However, the ionic conductivity of existing sulfide solid electrolytes is generally low, which limits their application in actual batteries. Summary of the Invention

[0005] The main object of the present invention is to propose a sulfide solid electrolyte, aiming to solve the problem of low ionic conductivity of sulfide solid electrolytes in the prior art.

[0006] To achieve the above object, the present invention proposes a sulfide solid electrolyte, and the composition of the sulfide solid electrolyte is Li 5+(5-b)a P 1-a M a S4X2;

[0007] Wherein, M includes at least one of alkali metals, alkaline earth metals, and transition metals;

[0008] X is one or more of F, Cl, and Br;

[0009] The value range of a is 0 < a < 1, and the value range of b is 0 < b < 5.

[0010] In one embodiment, the particle size of the sulfide solid electrolyte is less than 10 μm; and / or,

[0011] The ionic conductivity of the sulfide solid electrolyte is 10 -2 ~10 -3 S / cm; and / or,

[0012] The M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Zn, Cu, Au, Ag, Mo, Al, Ga, Cd, La, Zr, Y, Ti, Ni, Co, Mn, Cr, Fe, Ge, and In.

[0013] The present invention also provides a method for preparing a sulfide solid electrolyte, comprising the following steps:

[0014] S10, mixing a lithium source, a phosphorus source, an M source, a sulfur source and an X source, and performing ball milling to obtain a precursor powder;

[0015] S20, subjecting the precursor powder to vacuum calcination and grinding treatments in sequence to obtain the sulfide solid electrolyte.

[0016] In one embodiment, the lithium source comprises one or more of LiH, Li2S, LiCl; and / or,

[0017] The phosphorus source includes one or more of P2S5, P2S5, P4, P4S3Cl2 and Zn3P2; and / or,

[0018] The M source includes one or more of ZnS, CoS, FeS and CdS; and / or,

[0019] The sulfur source includes one or more of Li2S, P2S5 and ZnS; and / or,

[0020] The X source includes one or more of LiCl, ZnCl2 and FeCl2.

[0021] In one embodiment, step S10 includes:

[0022] S01, mixing a lithium source, a phosphorus source, an M source, a sulfur source and an X source, grinding them, and then adding a ball milling medium to perform ball milling to obtain a first powder;

[0023] S02, grinding the first powder, and then ball milling it to obtain a second powder;

[0024] S03, grinding the second powder to obtain the precursor powder.

[0025] In one embodiment, in step S01 and / or step 02, the ball milling treatment includes ball milling at 300-700 rpm for 20-40 minutes, pausing for 20-40 minutes, and then continuing the ball milling; the total duration of the ball milling treatment is 4-6 hours; and / or,

[0026] In step S01, step 02 and / or step 03, the grinding treatment time is 10 to 20 minutes.

[0027] In one embodiment, in step S01 and / or step 02, the ball milling media includes zirconia beads, glass beads or ceramic beads.

[0028] In one embodiment, the ball milling medium includes zirconia beads, and the zirconia beads include first zirconia beads and second zirconia beads. The particle size of the first zirconia beads is 9-10 mm, and the number of the first zirconia beads is 12-16. The particle size of the second zirconia beads is 3-4 mm, and the number of the second zirconia beads is 18-22.

[0029] In one embodiment, in step S20, the temperature of the vacuum calcination treatment is 500-550° C.; and the time of the vacuum calcination treatment is 1-3 hours.

[0030] The present invention also provides a use of the aforementioned sulfide solid electrolyte or the sulfide solid electrolyte prepared by the aforementioned method for preparing the sulfide solid electrolyte in preparing a lithium ion battery.

[0031] In the technical solution of the present invention, doping with the metal element M can improve the stability of the sulfide solid electrolyte on the one hand; on the other hand, it can regulate the movement mode of other elements in the lattice, thereby improving the lithium ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0033] Figure 1 X-ray diffraction patterns of the sulfide solid electrolytes in Example 1 and Comparative Example 1 provided by the present invention and the sulfide solid electrolytes calculated theoretically;

[0034] Figure 2 The LZPSCl crystal structure diagram calculated for the material provided by the present invention;

[0035] Figure 3 This is a graph showing the interfacial impedance detection results of the sulfide solid electrolyte in Example 1 and Comparative Example 1 provided by the present invention.

[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0037] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be described clearly and completely below. Those not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments not indicated by the manufacturer are all conventional products that can be obtained through commercial purchase. In addition, the meaning of "and / or" appearing throughout the text includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or a solution that satisfies both A and B simultaneously. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of those of ordinary skill in the art to implement. When the combination of technical solutions results in contradictions or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.

[0038] A solid-state electrolyte (SSE) refers to a solid material used as an ion conductor in electrochemical devices. Compared with traditional liquid electrolytes, it has higher safety, a wider operating temperature range, and better mechanical stability.

[0039] Solid-state electrolytes include oxide-based solid-state electrolytes, sulfide-based solid-state electrolytes, and polymer-based solid-state electrolytes. Among them, sulfide-based solid-state electrolytes such as LPS (Li2S-P2S5) have good flexibility and are easy to process into thin films.

[0040] However, the ionic conductivity of existing sulfide solid-state electrolytes is generally low, which limits their application in actual batteries.

[0041] In view of this, the present invention provides a sulfide solid-state electrolyte, and the composition of the sulfide solid electrolyte is Li 5+(5-b)a P 1-a M a S4X2; wherein, M includes at least one of alkali metals, alkaline earth metals, and transition metals; X is one or more of F, Cl, Br; the value range of a is 0 < a < 1, and the value range of b is 0 < b < 5.

[0042] In the technical solution of the present invention, introducing the M metal element into the sulfide solid-state electrolyte can, on the one hand, improve the stability of the sulfide solid-state electrolyte; on the other hand, it can regulate the movement mode of other elements in the lattice, thereby improving the lithium-ion conductivity.

[0043] In some embodiments of the present invention, the particle size of the sulfide solid electrolyte is less than 10 μm. The particle size of the sulfide solid electrolyte can be 0.5 μm, 1 μm or 3 μm. The particle size within the above range can ensure that the interface impedance between the sulfide solid electrolyte particles is small, the ion conductivity is high, and the cycle stability and energy density of the battery are improved.

[0044] In some embodiments of the present invention, the ionic conductivity of the sulfide solid electrolyte is 10 -2 ~10 -3 S / cm. The ionic conductivity of the sulfide solid electrolyte can be 10 -2 S / cm or 10 -3 S / cm, and its ionic conductivity within the above range can ensure the battery's charge and discharge rate, power density and overall performance are good.

[0045] In some embodiments of the present invention, M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Zn, Cu, Au, Ag, Mo, Al, Ga, Cd, La, Zr, Y, Ti, Ni, Co, Mn, Cr, Fe, Ge and In. It should be noted that the M metal element can be any one of Na (sodium), K (potassium), Rb (rubidium), Cs (cesium), Be (beryllium), Mg (magnesium), Ca (calcium), Sr (strontium), Ba (barium), Zn (zinc), Cu (copper), Au (gold), Ag (silver), Mo (molybdenum), Al (aluminum), Ga (gallium), Cd (cadmium), La (lanthanum), Zr (zirconium), Y (yttrium), Ti (titanium), Ni (nickel), Co (cobalt), Mn (manganese), Cr (chromium), Fe (iron), Ge (germanium) and In (indium), and can also be two or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Zn, Cu, Au, Ag, Mo, Al, Ga, Cd, La, Zr, Y, Ti, Ni, Co, Mn, Cr, Fe, Ge and In, all within the scope of protection of the present invention. The M metal element is preferably Zn, and the addition of zinc will improve the mechanical strength of the sulfide solid electrolyte.

[0046] The present invention also provides a method for preparing a sulfide solid electrolyte, comprising the following steps: S10, mixing a lithium source, a phosphorus source, an M source, a sulfur source and an X source, and subjecting the mixture to ball milling to obtain a precursor powder; S20, sequentially subjecting the precursor powder to vacuum calcination and grinding to obtain the sulfide solid electrolyte.

[0047] In the technical solution of the present invention, according to Li 5+(5-b)a P 1-a M aThe lithium source, phosphorus source, M source, sulfur source and X source are weighed in the stoichiometric ratio of S4X2, and ball milling and vacuum calcination are performed to allow the M metal element to enter the lattice structure of the sulfide solid electrolyte by doping or substitution to adjust its ionic conductivity. Among them, the ball milling treatment is to mix and grind the raw material powders into nano-scale or submicron particles by a high-energy ball mill. During the ball milling process, mechanical energy is converted into chemical energy, which prompts the raw materials to react and form the target compound. The ball-milled powder is subjected to vacuum calcination treatment, which further promotes the chemical reaction between the raw materials to form a stable sulfide solid electrolyte. Vacuum calcination can be carried out in an environment where air and moisture are excluded to avoid adverse reactions between sulfide materials and oxygen or water vapor.

[0048] In some embodiments of the present invention, the lithium source includes one or more of LiH, Li2S, and LiCl. That is, the lithium source can be any one of LiH, Li2S, and LiCl, or two or more of LiH, Li2S, and LiCl, all within the scope of the present invention. The selection of the lithium source can be flexibly adjusted according to the specific preparation process and application requirements.

[0049] In some embodiments of the present invention, the phosphorus source includes one or more of P2S5, P4, P4S3Cl2 and Zn3P2. That is, the phosphorus source can be any one of P2S5, P4, P4S3Cl2 and Zn3P2, or two or more of P2S5, P4, P4S3Cl2 and Zn3P2, all within the scope of the present invention. The selection of the phosphorus source can be flexibly adjusted according to the specific preparation process and application requirements.

[0050] In some embodiments of the present invention, the M source includes one or more of ZnS, CoS, FeS and CdS. That is, the M source can be any one of ZnS, CoS, FeS and CdS, or two or more of ZnS, ZnS, CoS, FeS and CdS, all within the scope of the present invention. The selection of the M source can be flexibly adjusted according to the specific preparation process and application requirements.

[0051] In some embodiments of the present invention, the sulfur source includes one or more of Li2S, P2S5 and ZnS. That is, the sulfur source can be any one of Li2S, P2S5 and ZnS, or two or more of Li2S, P2S5 and ZnS, all within the protection scope of the present invention. The selection of the sulfur source can be flexibly adjusted according to the specific preparation process and application requirements.

[0052] In some embodiments of the present invention, the X source includes one or more of LiCl, ZnCl2 and FeCl2. That is, the X source can be any one of LiCl, ZnCl2 and FeCl2, or two or more of LiCl, ZnCl2 and FeCl2, all within the scope of the present invention. The selection of the X source can be flexibly adjusted according to the specific preparation process and application requirements.

[0053] In some embodiments of the present invention, step S10 includes: S01, mixing a lithium source, a phosphorus source, an M source, a sulfur source and an X source, grinding them, and then adding a ball milling medium for ball milling to obtain a first powder; S02, grinding the first powder, and then ball milling it to obtain a second powder; S03, grinding the second powder to obtain the precursor powder.

[0054] In the technical solution of the present invention, the powder particle size is reduced by grinding + ball milling, and the raw materials are dispersed more evenly to avoid agglomeration. The particle size is further refined by ball milling, the specific surface area of ​​the raw materials is increased, and the subsequent reaction is promoted. The grinding treatment after the first ball milling treatment is to prevent the high temperature generated during the ball milling process from causing the powder to agglomerate more and affect the subsequent chemical reaction. In step S03, the powder after the second ball milling is ground to ensure that the subsequent vacuum high-temperature calcination is more thorough.

[0055] In some embodiments of the present invention, in step S01 and / or step 02, the ball milling process includes ball milling at 300-700 rpm for 20-40 minutes, pausing for 20-40 minutes, and then continuing the ball milling process; the total duration of the ball milling process is 4-6 hours. Intermittent ball milling is to prevent the powder from agglomerating into larger particles. During each pause, the powder particles have a chance to rearrange, avoiding the problem of local uneven composition.

[0056] In some embodiments of the present invention, in step S01, step 02 and / or step 03, the grinding time is 10 to 20 minutes. The grinding time within the above range can ensure that the raw material particles are small and convenient for reaction.

[0057] In some embodiments of the present invention, in step S01 and / or step 02, the ball milling medium includes zirconium oxide beads, glass beads or ceramic beads. The ball milling medium can help the raw material powder to be efficiently ground and mixed by the transfer of mechanical energy, ensuring that the final product has a more uniform component distribution and an ideal particle size.

[0058] In some embodiments of the present invention, the ball milling medium includes zirconia beads, the zirconia beads include first zirconia beads and second zirconia beads, the particle size of the first zirconia beads is 9 to 10 mm, the number of the first zirconia beads is 12 to 16, the particle size of the second zirconia beads is 3 to 4 mm, and the number of the second zirconia beads is 18 to 22. By using zirconia beads with different particle sizes, more efficient grinding and mixing effects can be achieved during the ball milling process.

[0059] In some embodiments of the present invention, in step S20, the temperature of the vacuum calcination treatment is 500-550°C; the time of the vacuum calcination treatment is 1-3 hours. The temperature and time of the vacuum calcination treatment within the above range can effectively promote the synthesis reaction of the sulfide solid electrolyte and ensure that the crystallinity, purity and ionic conductivity of the sulfide solid electrolyte are good.

[0060] The present invention also provides an application of the aforementioned sulfide solid electrolyte or the sulfide solid electrolyte prepared by the aforementioned method for preparing the sulfide solid electrolyte in preparing a lithium ion battery. The application includes all the beneficial effects of the sulfide solid electrolyte and the method for preparing the sulfide solid electrolyte, which will not be described one by one here.

[0061] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0062] Example 1

[0063] A method for preparing a sulfide solid electrolyte comprises the following steps:

[0064] 1. Material preparation: mortar, mortar rod, ball mill jar dried in a vacuum drying oven at 100°C the night before, 20 large zirconia beads (particle size 10mm), 14 small beads (particle size 4mm);

[0065] Check the glove box samples: Li2S, P2S5, LiCl anhydrous grade, more than 99% purity.

[0066] 2. Quickly transfer the mortar from the vacuum drying oven (100°C) to the glove box.

[0067] 3. Weigh the molar ratio of Li2S:P2S5:ZnS:LiCl = 1.8:0.4:0.2:2 in the glove box, grind in a mortar for 20 minutes, put the powder into a ball mill, add zirconium oxide ball mill (20 large beads, 14 small beads), seal the ball mill, and then ball mill at 500rpm for 30 minutes, stop for 30 minutes, and continue ball milling. After a total of 5 hours of ball milling (total time of ball milling + pause), open the ball mill in the glove box. At this time, the powder agglomerates and lumps. Put the lumps into the mortar and grind them again, then put them into the ball mill and ball mill for another 5 hours. The ball milling conditions are the same as the first ball milling. After the second ball milling for 5 hours, open the ball mill, take out the lumps, put them into the mortar and grind them to obtain the precursor powder.

[0068] 4. Transfer the precursor powder to a glass tube, seal it with a vacuum transfer device, and seal the tube outside the glove box. After sealing the tube, place it in a muffle furnace and calcine it at 510°C for 2 hours. Then take out the glass tube and put it into the glove box. At this time, the SSE is severely agglomerated. Grind it vigorously with a mortar to powder to obtain a sulfide solid electrolyte, which is recorded as Li 5.6 P 0.8 Zn 0.2 S4Cl2.

[0069] Comparative Example 1

[0070] Compared with Example 1, Comparative Example 1 is different in that:

[0071] In step 3: weigh the molar ratio of LiCl: P2S5: Li2S = 1.6: 0.5: 1.9 in the glove box to replace the sulfide solid electrolyte obtained, and record it as Li 5.4 PS 4.4 Cl 1.6 .

[0072] Performance Testing

[0073] The X-ray diffraction patterns of the sulfide solid electrolyte in Example 1 and Comparative Example 1 and the theoretically calculated sulfide solid electrolyte were compared, and the results are as follows: Figure 1 shown.

[0074] Depend on Figure 1 It can be seen that from top to bottom are the synthesized LZPSCl, LPSCl and the standard spectra calculated for LPSCl. From the results, the LPSCl series of solid electrolytes were successfully synthesized. In addition, Zn was successfully doped into it to obtain LZPSCl.

[0075] Figure 2 The LZPSCl crystal structure diagram calculated for the material shows the distribution of various elements. Especially after doping with metal elements, more interstitial lithium atoms appear around the metal atoms, which is beneficial to enhance the ionic conductivity.

[0076] The interface impedance of the sulfide solid electrolyte in Example 1 and Comparative Example 1 was detected by assembling a symmetrical battery of stainless steel to stainless steel using a solid electrolyte mold of CLUDE, placing the sulfide solid electrolyte under a pressure of 2 tons, and measuring the impedance data using Chenhua CHI604. The results are as follows: Figure 3 shown.

[0077] Depend on Figure 3 It can be seen that under the same environment (same pressure, temperature, humidity) and test conditions, after adding the Zn element, the interfacial impedance of the sulfide solid electrolyte is reduced to about one tenth of the original, and the ionic conductivity also becomes ten times the original accordingly.

[0078] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A sulfide solid electrolyte, characterized in that: The composition of the sulfide solid electrolyte is Li 5+(5-b)a P 1- a M a S4X2; Among them, M includes at least one of alkali metals, alkaline earth metals, and transition metals; X is one or more of F, Cl, and Br; The value range of a is 0 < a < 1, and the value range of b is 0 < b < 5.

2. The sulfide solid electrolyte according to claim 1, characterized in that The particle size of the sulfide solid electrolyte is less than 10 μm; and / or, The ionic conductivity of the sulfide solid electrolyte is 10 -2 ~10 -3 S / cm; and / or, The M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Zn, Cu, Au, Ag, Mo, Al, Ga, Cd, La, Zr, Y, Ti, Ni, Co, Mn, Cr, Fe, Ge, and In.

3. A method for preparing a sulfide solid electrolyte as claimed in claim 1 or 2, characterized in that: It includes the following steps: S10. Mix a lithium source, a phosphorus source, an M source, a sulfur source, and an X source, and perform ball milling to obtain a precursor powder; S20. Subject the precursor powder to vacuum calcination treatment and grinding treatment in sequence to obtain the sulfide solid electrolyte.

4. The method for preparing a sulfide solid electrolyte according to claim 3, characterized in that: The lithium source includes one or more of LiH, Li2S, and LiCl; and / or, The phosphorus source includes one or more of P2S5, P4, P4S3Cl2, and Zn3P2; and / or, The M source includes one or more of ZnS, CoS, FeS, and CdS; and / or, The sulfur source includes one or more of Li2S, P2S5, and ZnS; and / or, The X source includes one or more of LiCl, ZnCl2, and FeCl2.

5. The method for preparing a sulfide solid electrolyte according to claim 3, characterized in that: Step S10 includes: S01. Mix a lithium source, a phosphorus source, an M source, a sulfur source, and an X source, perform grinding treatment, and then add a ball milling medium for ball milling to obtain a first powder; S02. Grind the first powder and then perform ball milling to obtain a second powder; S03. Grind the second powder to obtain the precursor powder.

6. The method for preparing a sulfide solid electrolyte according to claim 5, characterized in that: In step S01 and / or step 02, the ball milling includes ball milling at 300 - 700 rmp for 20 - 40 min and then pausing for 20 - 40 min, and then continuing ball milling; the total duration of the ball milling is 4 - 6 h; and / or, In step S01, step 02, and / or step 03, the duration of the grinding treatment is 10 - 20 min.

7. The method for preparing a sulfide solid electrolyte according to claim 5, characterized in that: In step S01 and / or step 02, the ball milling medium includes zirconia beads, glass beads, or ceramic beads.

8. The method for preparing a sulfide solid electrolyte according to claim 7, characterized in that: The ball milling medium includes zirconia beads. The zirconia beads include first zirconia beads and second zirconia beads. The particle size of the first zirconia beads is 9 - 10 mm, the number of the first zirconia beads is 12 - 16, the particle size of the second zirconia beads is 3 - 4 mm, and the number of the second zirconia beads is 18 - 22.

9. The method for preparing a sulfide solid electrolyte according to claim 3, characterized in that: In step S20, the temperature of the vacuum calcination treatment is 500 - 550 °C; the time of the vacuum calcination treatment is 1 - 3 h.

10. Use of a sulfide solid electrolyte prepared by the preparation method of the sulfide solid electrolyte according to any one of claims 1 to 2 or the sulfide solid electrolyte according to any one of claims 3 to 9 in the preparation of a lithium ion battery.

Citation Information

Cited By

  • Doping modified sulfide electrolyte and preparation method thereof

    CN120657236A